Political power and authority in the art of sculpture in the new Assyrian era (911-612 BC) - Chro Bestun Hamad; Nihman Jumha Ibrahim (QALAAI ZANIST JOURNAL, 2022)
The Assyrians are considered one of the Semitic peoples who inhabited the northeastern part of Mesopotamia at the beginning of the third millennium BC. They were able to establish a sprawling empire. In building the civilization of Mesopotamia. This research came to present a picture of the aspect of the nature of the Assyrian system of government related to the supremacy of kings and their military activities through the art of sculpture, which is one of the Assyrian art that reflects the political and military conditions of the modern Assyrian empire for the period from 911 (-612 BC). The art of modern Assyrian sculpture was distinguished by the diversity of its subjects, and it represented an official imperial art, and most of its artistic scenes were devoted to dealing with the political aspect and expressing the personality of the king and his authority, displaying their military activities and depicting their victories on the fronts of fighting against their enemies. The souls of their enemies and how they deal with their opponents. Several models of various sculpted scenes dealing with themes of politics and military campaigns throughout the vast Assyrian Empire from 911-612 BC were displayed.